Prospective study to assess the survival outcomes of planned irradiation of ipsilateral subventricular and periventricular zones in glioblastoma - Valiyaveettil, Deepthi (Ecancermedicalscience, 2020)
PURPOSE/OBJECTIVE(S): Retrospective evidence suggests that the irradiation of stem cells in the periventricular zone (PVZ), specifically the subventricular zone (SVZ), to higher doses may be associated with improved outcomes. MATERIALS/METHODS: This was a prospective study, done from 2012 to 2017 in glioblastoma patients to assess the efficacy of planned irradiation of ipsilateral PVZ and SVZ on survival outcomes. The clinical target volume included the tumour bed with a 1.5–2 cm margin, perilesional oedema and was expanded to encompass the ipsilateral PVZ (5 mm lateral expansion adjacent to the ventricles, including the SVZ, which was a 5 mm expansion lateral to lateral ventricle). The ipsilateral PVZ was planned to receive a dose of ≥50 Gy. RESULTS: 89 patients were recruited of which 74 patients were available for the analysis. Median age was 48 years. Mean doses to ipsilateral PVZ and SVZ were 56.2 and 55.1Gy, respectively. Median overall survival in the entire group was 13 months. There was no significant correlation between survival and doses to ipsilateral, contralateral, or bilateral PVZ and SVZ. Median survival was 16, 12 and 6 months for Eastern Cooperative Oncology Group (ECOG) PS 1, 2 and 3, respectively (p = 0.05). CONCLUSION: Planned irradiation of potential stem cell niches in the ipsilateral cerebral hemisphere did not result in improved survival as suggested by retrospective studies. Doses to contralateral or bilateral PVZ or SVZ also did not influence survival.